Close insecurity: shifting conceptions of security in prison confinement - Frois, C. (2016)
The study of security within a prison environment implies the observation of a complex phenomenon: on the one hand, inmates are defined as agents of insecurity, insofar as they are the authors of criminal acts, which to the outside world represent everything that is perceived as a threat – in terms of the law, order and general well-being. On the other hand, the prison is often characterised as a space riddled with fear, uncertainty and insecurity, manifest in the everyday life of prisons. In this article, based on a two-year fieldwork in three Portuguese male prisons, I explore the meaning attributed to security from inmates’ perspectives and discourses. This analysis, which includes inmates with different ages, origins, types of crime and sentence length, as well as specificities inherent to the chosen field sites, allows us to expand and deepen our understanding of the significance of security within a population that is often excluded from this discussion, albeit invariably related with it.